Autoimmune Manifestations in Heterozygote Type I Complement 2 Deficiency: A Child Eventually Diagnosed With Systemic Lupus Erythematosus - Rabia Miray KIŞLA EKİNCİ and Sibel BALCI and Atil BİŞGİN and; iye ATMIŞ and; k DOĞRUEL and; afa YILMAZ (Archives of Rheumatology, 2019)
Systemic lupus erythematosus (SLE) is an autoimmune disorder resulting in a broad spectrum of manifestations in several organs, mainly skin and kidney. SLE occurs with interaction of genetic and environmental factors. The most remarkable genetic predisposition to SLE is deficiency of early components of the classical complement pathway. A five-year-old, previously healthy female patient was admitted to our hospital with headache, fever, focal partial seizure, diagnosed and treated as encephalitis. She was re-admitted to our hospital at six years of age with fever, fatigue, alopecia and oral aphthous ulcers and necrotizing vasculitis on extremities. Significant hypocomplementemia, anemia, proteinuria and positive autoantibodies and coombs test led to the diagnosis of SLE. Due to early disease onset and distinct autoimmune manifestations, we diagnosed our patient with type I complement 2 (C2) deficiency with a frameshift mutation in C2 gene and a serum C2 level of <0.2 mg/dL. To our knowledge, this is the first case of genetically confirmed and successfully treated hereditary C2 deficient SLE patient diagnosed with necrotizing vasculitis. We wish to highlight that distinctive autoimmune manifestations should guide physicians to research on monogenic lupus, particularly C2 deficiency, even in the absence of coexisting recurrent pyogenic infections.